2020
DOI: 10.1186/s12998-019-0290-7
|View full text |Cite
|
Sign up to set email alerts
|

Does manual therapy affect functional and biomechanical outcomes of a sit-to-stand task in a population with low back pain? A preliminary analysis

Abstract: Introduction: Manual therapy (MT) hypothetically affects discrepant neuromuscular control and movement observed in populations with low back pain (LBP). Previous studies have demonstrated the limited influence of MT on movement, predominately during range of motion (ROM) testing. It remains unclear if MT affects neuromuscular control in mobility-based activities of daily living (ADLs). The sit-to-stand (STS) task represents a commonlyperformed ADL that is used in a variety of clinical settings to assess functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Relationships based on cross‐sectional data between spinal amplitude and pain intensity were available for 74 studies with 5806 participants (Alschuler et al, 2009; Alves et al, 2020; Anderson et al, 2013; Ansari et al, 2014; Aure & Kvåle, 2022; Bazzaz‐Yamchi et al, 2021; Caporaso et al, 2012; Carpino et al, 2020; Carrasco‐Martínez et al, 2019; Christe et al, 2016; Coyle et al, 2017; de Brito Macedo et al, 2019; Demoulin et al, 2013; Du et al, 2017; Dubois et al, 2016; Duray et al, 2018; Fehrmann et al, 2017; Garcia et al, 2013; Geller et al, 2016; Grosdent et al, 2023; Grotle et al, 2004; Hidalgo et al, 2015; Hofste et al, 2021; Hrkać et al, 2022; Ibrahim et al, 2019; Jensen et al, 2010; Jette et al, 2016; Joshi et al, 2021; Kernan & Rainville, 2007; Kienbacher et al, 2017; Kiran et al, 2017; Larivière et al, 2022; Lenoir dit Caron et al, 2022; Louw et al, 2015; Louw, Farrell, et al, 2017; Louw, Zimney, et al, 2017; Mannion et al, 2001; Marich et al, 2017; Matheve et al, 2019; McCracken et al, 2002; Melikoglu et al, 2009; Mieritz et al, 2014; Miyachi et al, 2021; Neblett et al, 2013; Nemcić et al, 2013; Nordstoga et al, 2019; Olaogun et al, 2004; Ostelo et al, 2003; Osumi et al, 2019; Ozkaraoglu et al, 2020; Pagé et al, 2015; Papciak & Feuerstein, 1991; Peng et al, 2016; Preyde, 2000; Sakulsriprasert et al, 2011…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Relationships based on cross‐sectional data between spinal amplitude and pain intensity were available for 74 studies with 5806 participants (Alschuler et al, 2009; Alves et al, 2020; Anderson et al, 2013; Ansari et al, 2014; Aure & Kvåle, 2022; Bazzaz‐Yamchi et al, 2021; Caporaso et al, 2012; Carpino et al, 2020; Carrasco‐Martínez et al, 2019; Christe et al, 2016; Coyle et al, 2017; de Brito Macedo et al, 2019; Demoulin et al, 2013; Du et al, 2017; Dubois et al, 2016; Duray et al, 2018; Fehrmann et al, 2017; Garcia et al, 2013; Geller et al, 2016; Grosdent et al, 2023; Grotle et al, 2004; Hidalgo et al, 2015; Hofste et al, 2021; Hrkać et al, 2022; Ibrahim et al, 2019; Jensen et al, 2010; Jette et al, 2016; Joshi et al, 2021; Kernan & Rainville, 2007; Kienbacher et al, 2017; Kiran et al, 2017; Larivière et al, 2022; Lenoir dit Caron et al, 2022; Louw et al, 2015; Louw, Farrell, et al, 2017; Louw, Zimney, et al, 2017; Mannion et al, 2001; Marich et al, 2017; Matheve et al, 2019; McCracken et al, 2002; Melikoglu et al, 2009; Mieritz et al, 2014; Miyachi et al, 2021; Neblett et al, 2013; Nemcić et al, 2013; Nordstoga et al, 2019; Olaogun et al, 2004; Ostelo et al, 2003; Osumi et al, 2019; Ozkaraoglu et al, 2020; Pagé et al, 2015; Papciak & Feuerstein, 1991; Peng et al, 2016; Preyde, 2000; Sakulsriprasert et al, 2011…”
Section: Resultsmentioning
confidence: 99%
“…Relationships based on cross-sectional data between spinal amplitude and pain intensity were available for 74 studies with 5806 participants (Alschuler et al, 2009;Alves et al, 2020;Anderson et al, 2013;Ansari et al, 2014;Aure & Kvåle, 2022;Bazzaz-Yamchi et al, 2021;Caporaso et al, 2012;Carpino et al, suggesting that a larger spinal amplitude was associated with a lower pain intensity (Figure 4). Heterogeneity was moderate (I 2 = 51.0%, Qstatistic: p < 0.001).…”
Section: Main Analysesmentioning
confidence: 99%
“…With the development of spinal abnormalities, the muscles of one side become short and the other side becomes weak. As a result of this condition, there is a lack of coordination or muscle imbalance between these muscles during activity, and inappropriate movement patterns would be created (32,33). Restriction of spinal movement in people with low back pain may also decrease balance in these people, because with the motor restriction in the spine during the balance tests, the spine cannot perform the necessary movements and the person may have an impaired balance (34).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence to suggest that manual therapy techniques have a positive neurophysiological effect on pain and disability levels [43]. Regarding the effects on biomechanics, recent evidence has also demonstrated that performance of functional movement tasks (sit to stand) by patients with low back pain may be acutely altered following manual therapy intervention (combination of mobilization and manipulation) targeted toward the lumbar spine and pelvis [44]. Bearing in mind that manual therapy has a positive neurophysiological and biomechanical effect, it could be assumed that it could potentially improve the gait characteristics of low back pain patients, although there is no evidence to support this.…”
Section: Introductionmentioning
confidence: 99%